REVIEW JURNAL POTENSI PEMANFAATAN SERAT PINANG (Areca catechu L.) SEBAGAI BAHAN BAKU PEMBUATAN KERTAS SENI - Rasyidah Rasyidah Rasyidah (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2020)
Areca belongs to the species Areca catechu L. under Arecaceae family believed to have its better formability, abundant, renewable, cost-effective and eco-friendly features. Areca catechu L. has natural fiber that intensely studied in the last years due to their specific properties and their positive environmental impact. This paper exhibits an outline on natural fibers of Areca catechu spathe and husk fiber which is an agricultural waste as a part of different commercial and engineering applications. The researchers have reported that Areca catechu spathe and husk fiber consists of cellulose, hemicellulose, and lignin. It provide a potential use of natural fibers for make art paper. Therefore the determination of the chemical composition and stages of treatment for make pulp of the Areca catechu spathe and husk fiber is essential.